2018
DOI: 10.1186/s40463-017-0247-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of the BRAF mutation in papillary thyroid carcinoma and chronic lymphocytic thyroiditis

Abstract: BackgroundThe purpose of this study was to examine the possible prognostics and clinicopathologic characteristics underlying the BRAFV600E mutation and papillary thyroid carcinoma (PTC) coexisting or in absence of chronic lymphocytic thyroiditis (CLT).MethodsThis study was conducted on 172 patients who had undergone total thyroidectomy or unilateral total thyroidectomy for PTC; the patients were then examined for the BRAFV600E mutation using specimens obtained after their surgery from January 2013 to August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
4
16
0
1
Order By: Relevance
“…However, the higher frequency could also be attributed to tumors in patients from specific geographic locations and to methodologic differences. Recent studies from eastern Asia demonstrated a higher frequency of approximately 80% for the BRAF V600E mutation in PC, which is consistent with our results (24)(25)(26)(27). Residents in eastern Asia commonly consume seaweeds as a part of their regular diet.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the higher frequency could also be attributed to tumors in patients from specific geographic locations and to methodologic differences. Recent studies from eastern Asia demonstrated a higher frequency of approximately 80% for the BRAF V600E mutation in PC, which is consistent with our results (24)(25)(26)(27). Residents in eastern Asia commonly consume seaweeds as a part of their regular diet.…”
Section: Discussionsupporting
confidence: 92%
“…The use of NGS could be associated with the higher frequency of the BRAF V600E mutation in patients with PC noted in the present study. To date, the frequency of the BRAF V600E mutation in patients with PC has been analyzed using Sanger sequencing (SGS) with FFPE (21,26), SGS with frozen tissue (32,33), pyrosequencing (34) and real-time PCR (27). In the present study, we analyzed FFPE tissue sections obtained from 50 patients with TC using an Illumina Miseq sequencer.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the discovery of mutations involving the MAPK pathway in PLCH has transformed our understanding of the field and firmly established PLCH as a neoplasm. The MAPK mutations found in the PLCH lesions are similar to mutations found in other malignancies such as melanoma, 47 hairy cell leukemia, 48 papillary thyroid cancer, 49 as well as other histiocytic disorders such as ECD. 50 The most common mutation described in PLCH is the BRAF V600E mutation, present in 50% of the patients.…”
Section: Plch Is An Inflammatory Neoplasmsupporting
confidence: 63%
“…These play an important part in the tumor dedifferentiation reducing efficacy of RAI. [123][124][125] The extensive mechanism of actions of these mutations are beyond the scope of the review and can be found elsewhere.…”
Section: Treatment Of Radioiodine Refractory Metastatic Diseasementioning
confidence: 99%